XWare: a Middleware for Smart Retrofitting in Maintenance. Issue 19 (2022) - Sanchez-Londono, David; Barbieri, Giacomo; Garces, Kelly
Abstract: The management of industrial maintenance has rapidly evolved in the past few decades. Thanks to the advancements of Cyber-Physical Systems (CPSs) brought by Industry 4.0, the present and future health state of machines can be estimated and, as a result, smart maintenance based on real-time sensor data has emerged. One way to implement CPSs in an enterprise is through smart retrofitting: the integration of new technologies into legacy devices to enable CPS capabilities. Among these capabilities, communication involves the integration, translation and transmission of data from legacy devices to external applications. In this work, XWare (eXperimental middleWare) is proposed as a low-cost middleware for smart maintenance applications that eases the implementation of the communication capability into legacy devices. This implementation is enabled through the integration of various open-source technologies: MQTT, OM2M, and a custom-made library of Python functions. The integration of these components allows sensors placed on different locations to transmit maintenance-related data to a local server through the use of gateways. By methodically designing, implementing and verifying XWare, a scalable, easy to deploy, and open-source middleware for smart retrofitting in maintenance was developed.